Moderators of two dual eating disorder and obesity prevention programs. (July 2019) - Stice, Eric; Desjardins, Christopher D.; Shaw, Heather; Rohde, Paul
Abstract: Few trials have investigated factors that moderate the effects of eating disorder and obesity prevention programs, which may inform inclusion criteria and intervention refinements. We examined factors hypothesized to moderate the effects of the Healthy Weight eating disorder/obesity prevention program that promotes gradual healthy changes, and Project Health that adds cognitive dissonance activities. College students at risk for both outcomes because of weight concerns ( N  = 364, 72% female) were randomized to these interventions or an educational video condition, completing pretest, posttest, and 6, 12, and 24-month follow-up assessments. Healthy Weight and Project Health produced significantly larger reductions in eating disorder symptoms versus video controls for individuals with higher negative affect, emotional eating, dietary fat/sugar intake, and perceived pressure to be thin. Project Health also produced significantly less increases in BMI versus video controls for individuals with lower negative affect. Results suggest that these interventions produce larger eating disorder symptom reductions for individuals at elevated risk for eating pathology but hint that weight gain prevention effects may be attenuated by elevated negative affect. Results imply that larger eating disorder symptom reductions will result when implemented with individuals with both weight concerns and one of the additionally identified risk factors. Highlights: Examined moderators of eating disorder/obesity prevention programs. Negative affect and emotional eating, fat/sugar intake amplified symptom reductions. Greater fat/sugar intake and pressure to be thin also amplified symptom reductions. Negative affect attenuated weight gain prevention effects. Results provide direction for future eating disorder and obesity prevention efforts.